'Blue boats' and 'reef robbers': A new maritime security threat for the Asia Pacific?. (10th October 2019) - Song, Andrew M.; Hoang, Viet Thang; Cohen, Philippa J.; Aqorau, Transform; Morrison, Tiffany H.
Abstract : Vietnamese 'blue boats' – small wooden‐hulled fishing boats – are now entering the territorial waters of Pacific Island countries and illegally catching high‐value species found on remote coastal reefs. Crossing several international boundaries and traversing a distance of over 5000 km, these intrusions have alarmed Oceanic countries, including Australia. Lacking administrative capacity as well as jurisdictional authority to effectively control the vast stretches of island coastlines individually, governments and intergovernmental bodies in the region have called for strengthened coordination of surveillance efforts while also pressuring Vietnam diplomatically. This paper reviews these latest developments and is the first to provide a focused assessment of the issue. Through the lens of Copenhagen School of securitisation theory, we analyse responses of national and regional actors and their portrayal in online media to understand how blue boats are constructed as a security threat within a narrative of maritime, food and human security. Arguably, Australia together with the Forum Fisheries Agency, who advise on the governance of offshore tuna resources, have so far acted most decisively – in a way that might see them extend their strategic role in the region. We propose a comprehensive empirical research agenda to better understand and manage this nascent, flammable and largely unpredictable inter‐regional phenomenon.